How Results of The Ability to Understand Physics on Newton's Motion Law Material using Guided Inquiry? - Ma'ruf Ma'ruf; Novita Maumude; Khaeruddin Khaeruddin (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2020)
The main problem in this research is how the results of the level of understanding of physics concepts on the aspect of translation through the guided incuri learning model? The type of this research is True Experimental Design by using Posttest-Only Control Design. The research instrument used was a test of understanding the concept of the translational aspects of physics in the form of essay questions. The population is 120 students from class X of SMKN Buyasuri, and the sample is X class students